Purchasing decision process and factors affecting green product purchase decision of green consumers - Archarungroj, Paiboon; Sirikutta, Supada (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2025)
The purpose of this research was to study the pre-purchasing decision process and factors influencing green consumers’ decision to purchase green products, comparing green product purchasing decisions classified by green product purchasing/consumption behavior type and by green consumer groups, and study behavior after purchasing/consuming green products that affects purchasing behavioral trends. Data were collected with a sample group of 400 consumers who had purchased and/or consumed green products aged 20 years and over, using a questionnaire as a tool. The research found that most of the samples were latent green consumers, followed by potential green consumers and real green consumers. The hypothesis testing results revealed that the pre-purchasing processes including information search and the evaluation of alternatives affect the decision to purchase green products. Factors affecting the decision to purchase green products Including experiences with green products, attitude towards green products, green product features and social influence, and active green consumers have more decision to buy green products than latent green consumers. In addition, post-purchasing/post-consuming green product behaviors including satisfaction and receiving benefits beyond expectations from green products statistically affects purchasing behavioral trends. Statistically significant This research can be used by business operators in planning digital marketing communication strategies to communicate to consumers.